MyIntegrated reading companion / Xavier Thayalan ... [et al.] - Thayalan, Xavier; Shanthi, Alice; Jane, Xavierine; Abd Karim, Norfazlika; Lim, Teck Heng
Mylntegrated Reading Companion is indeed a comprehensive companion for intermediate learners of English. The fundamental focus of this book is to help learners of English to improve their reading skills. This book offers insights and step-by-step approach by presenting learning items in easy language to ease comprehension of the content. The sequential arrangement of the book can assist learners to become effective readers by completing exercises from relatively easy to difficult tasks. There are also various language activities in each chapter that reinforces their reading skills. The grammar sections complement the learning of grammatical items in other language courses. The highlight of the book is reflective reading whereby students respond to stories written in the context of students' life. This book is best used with Mylntegrated Writing Companion in preparation for the Malaysian University English Test (MUET).